Hidden Consequences: Examining the Impact of NIL on Athlete Well-Being - Hailey Harris; Natasha T Brison; Marlene A Dixon (Journal of Applied Sports Management, 2021)
With the NCAA's NIL policy changes, many athletes will likely need to solve the issue of brand management, with many of them assuming the role themselves. Taking on this role will likely lead to even more investment in their athlete identity (i.e., role engulfment), which has negative consequences for the athlete (Hatteberg, 2020). Guided by the literature on role engulfment, this article investigates the hidden effects NIL may have on collegiate athletes and their well-being, along with various branding and legal implications.
Keywords: College Sports; Health; NCAA; Role Engulfment; Student-Athletes